On the Usefulness of Financial Ratios to Investors in Common Stock. - O'Connor, Melvin C. (The Accounting Review, 1973)
Abstract The article examines the usefulness of financial ratios to investors in common stock. It was assumed that the formation of expectations about future rate of return rankings was significant to investors. Thus, the explanatory relationships found to exist between financial ratios and rate of return on investment in common stock were tested for ability to predict rate of return rankings. By moving from unadjusted rate of return to market adjusted rate of return, strong evidence of a market effect on the rate of return yielded by a common stock was found.